CGIAR Seed Equal Initiative-TASAI workshop organized on measuring inclusive access to quality seed - Puskur, Ranjitha; Yila, Jummai (CGIAR Initiative on Seed Equal, 2023)
The CGIAR Seed Equal Initiative under Work Package 6 on scaling equitable access to quality seed, led by Ranjitha Puskur, partnered with The Africa Seed Access Index (TASAI Inc.) and convened a 3-day stakeholder validation workshop to present and receive feedback on the proposed set of indicators and data collection tools for measuring inclusive access to seeds. Organized from May 30 to June 01, 2023 in Nairobi, Kenya, the workshop was attended by 31 seed experts from Kenya, Uganda, Zimbabwe, and India, representing private seed companies, seed producer organizations, national seed trade associations, national gene banks, national and regional agricultural research institutions, and universities. At the end of the workshop, the participants assessed the set of indicators and proposed additional indicators to include affordability, willingness to pay for improved seed, access to finance/credit, access to land for planting, degree of engagement in community groups, proximity to agro-dealer or seed seller, and proximity to or access to a model farmer.